Model of secure routing based on determining the maximum number of disjoint paths to minimize the probability of compromise the confidential messages - Лемешко, А.В.; Еременко, А.С.; Персиков, А.В.; Слейман, Б. (Radiotekhnika, 2019)
The paper proposes a model of secure routing based on determining the maximum number of disjoint paths in order to minimize the probability of compromise the confidential messages transmitted in the infocommunication network. The proposed model is based on solving the optimization problem of Integer Linear Programming in the presence of linear constraints, Boolean routing variables, and variables determining the number of used routes that take integer values. It has been established that the model provides an increase in the level of network security in terms of the probability of compromise of transmitted messages when it is used to calculate the maximum number of disjoint paths when implementing secure routing.